Ratiometric Fluorescent Probes Based on Isosteviol with Identification of Maleic Acid in Starchy Foods - Xinye Qian; Chunling Zheng; Fang Zhang (Foods)
The rigid saddle-shaped framework of isosteviol provides a unique host–guest recognition cavity. For the first time, we have utilized isosteviol to construct fluorescent probes 4 and 5, achieving highly selective recognition of maleic acid and fumaric acid. The experimental results indicated that neither probe 4 nor probe 5 exhibited significant fluorescence changes when exposed to fumaric acid. However, both probes demonstrated distinct ratiometric fluorescence responses upon interaction with maleic acid. For maleic acid, probes 4 and 5 showed detection limits of 4.14 × 10−6 M and 1.88 × 10−6 M, respectively. Density functional theory (DFT) calculations and 1H NMR spectroscopy revealed that probes 4 and 5 formed stable intermolecular hydrogen bonds with maleic acid, contributing to the observed changes in fluorescence signals. Furthermore, maleic acid was successfully detected in starch-rich dietary samples, including potatoes, sweet potatoes, and corn, utilizing the sensing capabilities of probes 4 and 5. In conclusion, probes 4 and 5 hold significant potential for the development of fluorescence-based recognition systems for fumaric acid and maleic acid.